Crystal Structure Relation between Tetragonal and Orthorhombic CsAlD4: DFT and Time‐of‐Flight Neutron Powder Diffraction Studies. Issue 33 (29th October 2015) - Bernert, Thomas; Krech, Daniel; Kockelmann, Winfried; Felderhoff, Michael; Frankcombe, Terry J.; Weidenthaler, Claudia
Abstract: The crystal structures of orthorhombic and tetragonal CsAlD4 were refined from time‐of‐flight neutron powder diffraction data starting from atomic positions predicted from DFT calculations. The earlier proposed crystal structure of orthorhombic CsAlH4 is confirmed. For tetragonal CsAlH4, DFT calculations predicted a crystal structure in I 41 / amd as potential minimum structure, while from neutron diffraction studies of CsAlD4 best refinement is obtained for a disordered structure in the space group I 41 / a, with a = 5.67231(9) Å, c = 14.2823(5) Å. While the caesium atoms are located on the Wyckoff position 4 b and aluminium at Wyckoff position 4 a, there are two distinct deuterium positions at the Wyckoff position 16 f with occupancies of 50 % each. From this structure, the previously reported phase transition between the orthorhombic and tetragonal polymorphs could be explained. Abstract : The crystal structures of CsAlD4 polymorphs, which can be transferred form one form into the other by milling or heating, are studied by DFT calculations and TOF neutron diffraction. The minimum energy structure of the tetragonal form is predicted in I 41 / amd, but the experimental data point more likely to a disordered arrangement of deuterium atoms in I 41 / a .